PRIMARY CURVATURE IN THE MID-CONTINENT RIFT: PALEOMAGNETISM OF THE PORTAGE LAKE VOLCANICS (NORTHERN MICHIGAN, USA) - Hnat J.S.; van der Pluijm B.A.; van der Voo R. (My University, 2006)
Rocks of the North American Mid-Continent Rift (MCR) in the Keweenaw Peninsula of northern Michigan display a change in structural trend from east to west, varying in strike from 100° in the east to 35° farther west, before returning to a more east-west trend of 80° near Wisconsin. In general, curvature can be described either as of primary origin, meaning that the arc developed in its present curved state, or as of secondary origin, when the arc formed from an initially straighter geometry. A powerful tool in evaluating the origin and degree of curvature in any deformed belt is paleomagnetism, where coincident change in declination and strike is evidence for secondary curvature. Several paleomagnetic studies have been completed on rift-related sedimentary rocks, as well as lava flows, from the MCR in the Lake Superior region. Paleomagnetic directions for the sedimentary rocks vary much more in declination than in inclination, possibly reflecting a vertical axis rotation. If secondary rotation has affected the sedimentary rocks, then underlying volcanic rocks should also demonstrate a similar rotation. Thirty-one sites were collected from the Portage Lake Volcanics in the most highly curved part of the Keweenaw Peninsula in the Upper Peninsula of Michigan. Sites were chosen to maximize the variation in structural trend. Thermal demagnetization results showed two components in samples from most sites, a lower temperature A component (< 580 °C) as well as a higher temperature B component (> 580 °C). Both components were tested for primary remanence using a conglomerate test. The A component, carried by magnetite, passes the conglomerate test at a 95% confidence level, and is therefore considered a primary remanence. The B component, carried by hematite, fails at the 95% level and is considered a secondary magnetization. Most importantly, declination of the primary (A) magnetization between sites shows no correlation with strike, demonstrating that vertical axis rotations cannot explain the curvature of the Mid-Continent Rift. We conclude that curvature in the Lake Superior Region is a primary feature, likely reflecting a pre-existing zone of weakness that was exploited during rifting. © 2006 Elsevier B.V. All rights reserved.
Keywords: CURVED BELT; MIDCONTINENT RIFT; OROCLINE; PALEOMAGNETISM; PORTAGE LAKE VOLCANICS